Developing a Peer Support Protocol for Improving Veterans' Engagement to Computer-Delivered Cognitive Behavioural Therapy. Issue 3 (22nd March 2017) - Ray, John M.; Kemp, Lakiesha L.; Hubbard, Amanda; Cucciare, Michael A.
Abstract : Background: Computer-delivered cognitive behavioural therapy (cCBT) is an effective alternative to provider-delivered treatment for depression and anxiety, but high attrition poses a significant challenge to its use. Peer support is a feasible approach to improving cCBT engagement, but less is known about its acceptability among Veterans.Aims: To obtain feedback from Veterans ( n = 24) with depression and/or anxiety on their preferences for (a) activities of Veterans Administration Peer Support Specialists (VA PSS) in helping Veterans use Moving Forward, a cCBT-based protocol developed by VA, and (b) methods for delivering support to Veterans using this programme.Method: Four focus groups (5–7 Veterans per group) provided feedback to be used in the development of a peer-supported engagement intervention to help Veterans with depression and anxiety use Moving Forward. Content areas included roles that a VA PSS might play in supporting the use of and engagement in Moving Forward, as well as methods of delivering that support.Results: Veteran preferences for PSS activity focused on practical aspects of using Moving Forward, including orientation to the programme, technical support, and monitoring progress. Feedback also suggested that Veterans preferred more personal roles for the PSS, including emotional support, as well as application of Moving Forward to 'real life' problems.Conclusions: The findings extend the literature on online, patient-facing mental health protocols by identifying emotional support and 'real life' skills application as Veteran-preferred components of a peer-support protocol designed to enhance use of and engagement in cCBT for depression and anxiety.